The epidemiology of pancreatic disease in Portugal. - Dias, J A; Giria, J A (Acta Médica Portuguesa, 1995)
The authors describe the most relevant aspects of the occurrence, distribution and relative importance of the main diseases of the Pancreas in Portugal, comparing their incidence and mortality rates with other European countries in recent years. The main risk factors associated with pancreatic cancer are referred, stressing the appropriate preventive measures. Hospital management and cost-efficiency analysis of such patients are also estimated.